2002
DOI: 10.1039/b203414j
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of mercury in chemical fractions of contaminated urban soils of Middle Amur, Russia

Abstract: The distribution of mercury (Hg) in fractions of urban soils from two industrial cities in the Russian Far East which are subject to varying degrees of Hg contamination was examined. The speciation scheme applied was based on routine chemical extraction methods used in soil investigations. Such an approach enables the Hg data to be brought into correlation with soil basic fractions and the fate of Hg bound to different soil components to be followed. Humic acids and a non-hydrolysable residue (humin), i.e. the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…In urban soil, Hg concentrations can be higher than the geochemical background values of soil in rural areas [15]. Elevated concentrations of a few to several mg of Hg per kg of soil have been recorded in various cities around the world [16][17][18], typically attributed to anthropogenic sources of enrichment [19,20]. There is a general paucity of information in terms of Hg concentrations in the urban soil environment.…”
Section: Introductionmentioning
confidence: 98%
“…In urban soil, Hg concentrations can be higher than the geochemical background values of soil in rural areas [15]. Elevated concentrations of a few to several mg of Hg per kg of soil have been recorded in various cities around the world [16][17][18], typically attributed to anthropogenic sources of enrichment [19,20]. There is a general paucity of information in terms of Hg concentrations in the urban soil environment.…”
Section: Introductionmentioning
confidence: 98%
“…This concentration jump is indicative of a stage-by-stage process of Hg binding in soils at sites of different binding energy, the phenomenon described earlier [1,11,31]. Zvonarev and Zyrin [31] showed that at low concentrations, almost all Hg is sorbed at sites of high binding energy ( Figure 1, site A).…”
Section: Hg In Percolating Watersmentioning
confidence: 77%
“…The soil subsamples obtained were placed in polyethylene cans which were precleaned by soaking in 2% HNO 3 for 48 hours [1]. Below the soil layer, a drainage layer of washed and burnt sand was spread.…”
Section: Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations